Tumor necrosis factor-alpha inhibitor treatment for sarcoidosis - José Luis Callejas-Rubio; Lourdes López-Pérez; Norberto Ortego-Centeno (Dove Medical Press, 2008)
José Luis Callejas-Rubio, Lourdes López-Pérez, Norberto Ortego-CentenoUnit of Autoimmune Systemic Diseases, Hospital Clinico San Cecilio, Granada, SpainAbstract: Sarcoidosis is a chronic multisystem disease of unknown etiology, characterized by noncaseating granulomatous infiltration of virtually any organ system. Treatment is often undertaken in an attempt to resolve symptoms or prevent progression to organ failure. Previous studies have suggested a prominent role for tumor necrosis factor-alpha (TNF-α) in the inflammatory process seen in sarcoidosis. TNF-α and interleukin-1 are released by alveolar macrophages in patients with active lung disease. Corticosteroids have proved to be efficacious in the treatment of sarcoidosis, possibly by suppressing the production of TNF-α and other cytokines. Three agents are currently available as specific TNF antagonists: etanercept, infliximab, and adalimumab. Although data from noncomparative trials suggest that all three have comparable therapeutic effects in rheumatoid arthritis, their effects in a granulomatous disease such as sarcoidosis are less consistent. In this review, current data on the effectiveness are summarized.Keywords: sarcoidosis, infliximab, etanercept, adalimumab, anti-TNA alpha